KONSEP THAHARAH DALAM AL-QURAN: Studi Tafsir Maudhu’i - Hamnah, Hamnah (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
This study examines the concept of thaharah (purity) in the Qur'an through a thematic tafsir (interpretation). The aim of this study is to explore the meaning, scope, and implications of thaharah from a Qur'anic perspective, both in the physical and spiritual dimensions. The method used is the maudhu'i tafsir, which includes compiling all verses related to thaharah, analyzing the context in which the verses were revealed (asbab al-nuzūl), and interpreting them based on the opinions of classical and contemporary commentators.The results show that thaharah in the Qur'an encompasses not only external cleanliness such as ablution (wudu), bathing (ghusl), and tayammum (cleansing of the body). It also touches on the inner aspect, namely the purification of the heart and soul from shirk (polytheism), sin, and blameworthy traits. The concept of thaharah symbolizes the integration of physical and spiritual cleanliness, leading humans toward the perfection of faith and piety. Thus, purification is the primary foundation of a Muslim's worship and life, emphasizing the importance of cleanliness as a manifestation of faith and obedience to Allah SWT.